Horizontal inequality as a dependent variable - Carla Canelas; Rachel M. Gisselquist (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
A considerable body of research suggests that horizontal inequality between ethnic groups has major socioeconomic implications, in particular for peace and economic development. Much of this work focuses on horizontal inequality as an independent causal variable, rather than an outcome of various processes. In this paper we offer conceptual, theoretical, and empirical reasons for treating horizontal inequality as a dependent variable and challenging assumptions of fixity. We first consider explanations for variation drawing on the literature on horizontal inequality, as well as on ethnicity more broadly. We then explore how horizontal inequality can be measured using survey and census data and present analyses based on two datasets providing information on inequality in terms of educational attainment (HI-E) for the period 1960s-2000s. These data suggest both a general trend towards decline in HI-E over time and considerable regional variation. This paper serves also to introduce and frame the contributions to this special section, each of which speaks to horizontal inequality in a particular country and provides a focused look - using survey and census data - into patterns, trends, correlates, and implications of horizontal inequality at sub-national levels.
Keywords: J15; I24; D63; C80; 330; educational attainment; ethnic groups; group-based inequality; horizontal inequality; inequality